Cyberattacks and data breaches in Indonesia by Bjorka: hacker or data collector? - Tole Sutikno; Deris Stiawan (Institute of Advanced Engineering and Science, 2022)
Recently, the public has been shocked by the mysterious figure of Hacker Bjorka. Bjorka hacked Indonesian officials. Bjorka leaks Indonesia's General Election Commission (KPU) data. This raises a significant red flag concerning Bjorka's ability to